Associations of childhood and adulthood height and the components of height with insulin-like growth factor (IGF) levels in adulthood: 65 year follow-up of the Boyd Orr cohort. - Bray, Isabelle C.; Gunnell, David J.; Holly, Jeff M P; Middleton, Nicos; Smith, George Davey W; Martin, Richard Michael (My University, 2006)
Context: Taller individuals with longer legs have a higher risk of cancer but a lower risk of coronary heart disease. Objective: We investigated whether childhood height and its components are associated with the IGF system in adulthood. Design and Participants: We analyzed data from 429 participants of the Boyd Orr cohort, for whom height measured in childhood (mean age, 7.4 yr) in 1937–1939 could be related to levels of IGF-I, IGF-II, IGF binding protein (IGFBP)-2, and IGFBP-3 in adulthood (mean age, 71.1 yr). In 385 participants, measured height in adulthood could be related to IGF levels. Results: In fully adjusted models (controlling for age, sex, socioeconomic factors, lifestyle, and body mass index), childhood height and its components were not associated with adult circulating IGF-I, IGF-II, or IGFBP-2 levels. IGFBP-3 was 85.5 ng/ml higher (95% confidence interval, 11.6 to 182.5; P 0.08) per SD increase in childhood trunk length and 83.6 ng/ml lower (95% confidence interval, 10.3 to 177.5; P 0.08) per SD increase in childhood leg/trunk ratio. Height in adulthood was not associated with IGF-I, IGF-II, or IGFBP-3 and was inversely associated with IGFBP-2 (P 0.05) after additionally controlling for childhood height. Conclusion: There was no evidence that associations of childhood height with cancer and coronary heart disease risk are mediated by IGF-I in adulthood. The anthropometric associations with IGFBP-2 and IGFBP-3 could be chance findings but warrant additional investigation. IGF levels in childhood may be more important determinants of long-term disease risk than adult levels. (J Clin Endocrinol Metab 91: 1382–1389, 2006)